Glue embolisation of a bleeding pseudoaneurysm related to surgically-assisted rapid palatal expansion. Issue 6 (July 2019) - Maleux, O.; da Costa Senior, O.; Politis, C.; Maleux, G.
Abstract: Vascular injuries after orthognathic surgery are rare, and mainly occur in young adults after Le Fort I osteotomies. We report the case of a 14-year-old girl who presented with life-threatening epistaxis one week after a surgically-assisted rapid palatal expansion (SARPE) followed by activation of a transpalatal distractor. Definitive treatment was superselective, catheter-directed, glue-embolisation of a bleeding bilobar pseudoaneurysm, which was located at an end branch of the left sphenopalatine artery.